2020
DOI: 10.1101/2020.10.13.338319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cas9-AAV6 Gene Correction of Beta-Globin in Autologous HSCs Improves Sickle Cell Disease Erythropoiesis in Mice

Abstract: CRISPR/Cas9-mediated beta-globin (HBB) gene correction of Sickle Cell Disease (SCD) patient-derived hematopoietic stem cells (HSCs) in combination with autologous transplantation represents a novel paradigm in gene therapy. Although several Cas9-based HBB-correction approaches have been proposed, functional correction of in vivo erythropoiesis has not been investigated. Here, we used a humanized globin-cluster SCD mouse model to study Cas9-AAV6-mediated HBB-correction in functional HSCs within the context of a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Such an approach would also be highly applicable to settings where on-target mutations are detrimental and limit the curative potential of gene correction approaches, e.g. correction of the hemoglobin sickle allele (Wilkinson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach would also be highly applicable to settings where on-target mutations are detrimental and limit the curative potential of gene correction approaches, e.g. correction of the hemoglobin sickle allele (Wilkinson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The low allelic chimerism of Prkdc HDR and high abundance of Prkdc indel among myeloid cells demonstrate the challenge of ensuring that all hematopoietic cells are supplied by a genetically defined population of edited HSPCs. The potentially negative consequences of on-target indels has also recently been highlighted in other gene correction models (Wilkinson et al, 2021). This drawback inspired us to establish a single cell HSC expansion system that would allow sequence-based selection of bona fide HSCs at the clonal level.…”
Section: Gene-edited Hscs Correct Prkdc Scid Immunodeficiency But Bea...mentioning
confidence: 99%
“…Genetic manipulation to induce expression of HbF does not eliminate β S , and when mediated by double-stranded DNA breaks (DSBs), carries risks associated with uncontrolled mixtures of indels (insertions Article and deletion), translocations, loss of large chromosomal segments, chromothripsis, and p53 activation [13][14][15][16][17][18] (Supplementary References). Cas9 nuclease-mediated homology-directed repair can correct HBB S but is difficult to achieve efficiently in repopulating HSCs 19,20 and also requires DSBs. Elimination of the root cause of SCD by converting the HBB S allele to a benign variant without introducing DSBs could overcome these limitations.…”
mentioning
confidence: 99%
“…In this context, AAVs can remain episomal, however some studies have also shown vector integration through both non-homologous sites and homologous recombination [ 34 ]. Overall, these vectors can achieve long-term expression and are being combined with CRISPR (AAV-based CRISPR systems) to study potential treatments for β-hemoglobinopathies like sickle cell disease (ex vivo gene therapy) [ 35 ]. Another additional concern is the size of the gene that we aim to deliver.…”
Section: In Vivo Gene Therapy and Aav Vectorsmentioning
confidence: 99%